Od praw obywatelskich do praw człowieka - dylematy ewolucji polskiego systemu ochrony praw człowieka, prawo międzynarodowe: [From civil rights to human rights - the dilemmas of the evolution of the Polish human rights protection system] (Studia Prawnicze / The Legal Studies, 2002)
Autor artykułu przedstawia współczesne zagrożenia dla systemu praw człowieka, od terroryzmu po ograniczanie praw przez rządy w imię zwiększenia bezpieczeństwa. Autor przypomina czytelnikom podstawowe elementy koncepcji  „praw obywatelskich”, myślenie prawnicze w dobie PRL odnośnie „praw człowieka”, proces kształtowania się świadomości prawnej obywateli. Ponadto opisuje przełomowy okres transformacji ustrojowej w Polsce, w którym doszło do radykalnych zmian. Zwraca uwagę na wyzwania przed którymi staje współczesna Polska takie jak problem ograniczania wolności, powiązania praw z odpowiedzialnością oraz aktywność ochrony praw społeczno-ekonomicznych. The author of this article outlines contemporary threats to the human rights system, from terrorism to the limitations of rights by governments in the name of increasing security. The author reminds readers of the basic elements of the concept of “civil rights”, legal thinking related to “human rights” during the Communist era, and the formation process of legal awareness of the citizens. In addition, it describes the critical period of political transformation in Poland, during which radical changes took place. It draws attention to the challenges faced by contemporary Poland, such as the problem of limiting freedoms, the link between rights and responsibilities and the activity in the field of socio-economic rights protection.